Influence of Gender and School Location on Habitual and Behavioural Study among Secondary School Students in Lagos State - Abdulkareem, Habibat Bolanle (PEDAGOGIA, 2024)
This study examined the interplay between gender and school location in shaping study habits among secondary school students in Lagos State, with a focus on Alimosho Local Government Area. A sample of 800 senior secondary students was evaluated, with 80 purposively selected from three schools. Utilizing the Students’ Study Habits Inventory validated by Akinnade (2017), the research identified significant gender differences in study habits, with male students demonstrating more favorable habits than their female counterparts. This disparity underscores the influence of socio-cultural and educational factors on study behaviors. Although an association between school location and study habits was observed, it did not reach statistical significance (p 0.05). To address these findings, the study proposed targeted interventions, such as the Students’ Interactive Programme, designed to support female students during post-school hours. These initiatives aim to bridge the gender gap and promote equitable study habits. The study emphasizes the importance of considering gender and school location when designing policies and programs to foster effective study habits. By implementing targeted strategies, educational stakeholders can create a supportive learning environment that ensures academic success for all students, irrespective of gender or geographic context.